A new species of Menestho Møller, 1842 from the Arctic with remarks on Menestho albula (Fabricius, 1780) (Gastropoda: Heterobranchia: Pyramidellidae) - Nekhaev, Ivan O. (Zootaxa, 2017)
Nekhaev, Ivan O. (2017): A new species of Menestho Møller, 1842 from the Arctic with remarks on Menestho albula (Fabricius, 1780) (Gastropoda: Heterobranchia: Pyramidellidae). Zootaxa 4347 (1), DOI:10.11646/zootaxa.4347.1.13